Models for predicting changes in public opinion during the implementation of the narrative in social media - Romaniuk, Roman; Voitko, Oleksandr; Parkhuts, Liubomyr; Rakhimov, Volodymyr; Kostiak, Maryna (Національний технічний університет "Харківський політехнічний інститут", 2025)
In the modern world, social media are becoming the main channels of communication, which significantly affects the formation of public opinion and the implementation of strategic narratives. In the context of global information challenges, in particular war, understanding and predicting changes in public sentiment is extremely important for the effective implementation of state information policy, as well as for combating disinformation. The study showed that social media has a significant impact on public consciousness, and the use of information dissemination models, such as Bass's diffusion of innovations model, allows predicting the spread of narratives among different groups of users. The use of neural networks to analyze socio-political sentiment provided highly accurate forecasts with good quality indicators. The results of the study emphasize the importance of adapting content strategy in social media to increase the effectiveness of influencing the audience.

У сучасному світі соціальні медіа стають основними каналами комунікації, що суттєво впливає на формування громадської думки та реалізацію стратегічних наративів. У контексті глобальних інформаційних викликів, зокрема війни, розуміння та прогнозування змін суспільних настроїв є надзвичайно важливим для ефективної реалізації державної інформаційної політики, а також для боротьби з дезінформацією. Дослідження показало, що соціальні медіа мають значний вплив на громадську свідомість, і використання моделей розповсюдження інформації, таких як модель дифузії інновацій Басса, дозволяє прогнозувати поширення наративів серед різних груп користувачів. Використання нейронних мереж для аналізу суспільно-політичних настроїв забезпечило високоточні прогнози з хорошими показниками якості. Результати дослідження підкреслюють важливість адаптації контент-стратегії в соціальних медіа для підвищення ефективності впливу на аудиторію.
Моделі прогнозування змін громадської думки під час реалізації наративу в соціальних медіа
Keywords: public opinion; social media; strategic communications; diffusion of innovations; Bass mode; neural networks; disinformation; громадська думка; соціальні медіа; стратегічні комунікації; дифузія інновацій; модель Басса; нейронні мережі; дезінформація